1997
DOI: 10.1007/s002030050521
|View full text |Cite
|
Sign up to set email alerts
|

Purine metabolism and the microaerophily of Helicobacter pylori

Abstract: The requirements for purine nucleotide synthesis, the effects of purine analogues, and the metabolism of adenine in the bacterium Helicobacter pylori were investigated employing cell culture techniques and one-dimensional NMR spectroscopy. Bacterial cells grew and proliferated in media lacking preformed purines, indicating that H. pylori can synthesize purine nucleotides de novo to meet its requirements. Blocking of this pathway in the absence of sufficient preformed purines for salvage nucleotide synthesis le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…Purine salvage and utilization have previously been examined in H. pylori (18,49,50). Radiolabeling studies have been used to show uptake and incorporation of the purine bases adenine and guanine (and to a lesser extent, hypoxanthine) (50).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Purine salvage and utilization have previously been examined in H. pylori (18,49,50). Radiolabeling studies have been used to show uptake and incorporation of the purine bases adenine and guanine (and to a lesser extent, hypoxanthine) (50).…”
mentioning
confidence: 99%
“…The presence of adenine, guanine, and hypoxanthine phosphoribosyltransferase activities have been measured from whole-cell lysates (50), and an in-depth look at the enzymatic nature of H. pylori's purified xanthine-guanine phosphoribosyltransferase demonstrated its ability to catalyze the formation of 6-oxopurines (18). One study has shown that H. pylori can grow in the absence of preformed purines as long as exogenous catalase is present (49). It has been shown that exogenous catalase added to medium can increase the growth of H. pylori by preventing the formation of toxic peroxidation products from unsaturated fatty acids (29) and that bovine serum albumin (BSA) and catalase together can provide the minimal requirements by which H. pylori can grow on blood-or serum-free media (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adenine is the most prominent purine in the blood (22), and of all the purine bases, it has been shown to be the most rapidly taken up and processed into nucleotides by H. pylori (43). All these findings, including the more recent discovery of adenosine deaminase activity in at least three H. pylori strains (16,17,20), have pointed to adenine/adenosine being the prominent purine base/nucleoside utilized by this bacterium. However, recently an H. pylori ⌬guaA mutant was shown to have no colonization defects in a murine model of infection (20).…”
Section: Discussionmentioning
confidence: 99%
“…When grown in a defined medium derived by Reynolds and Penn (termed RnP medium) (15), purines were initially shown to be required for growth in strain NCTC 11637 as well as in eight clinical isolates. A subsequent study, however, reported that growth could be achieved in the absence of purines if the medium was supplemented with 0.1% catalase in strains NCTC 11639 and N6 and two low-passage-number clinical isolates (16). It was more recently shown that purines are required for growth in Reynolds and Penn's defined medium for strain G27 (17), and that catalase was incapable of restoring growth in purine-free media.…”
mentioning
confidence: 99%